2018
DOI: 10.1111/imj.13753
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of an age‐specific cut‐off for d‐dimer for pulmonary embolism assessment when used with various pulmonary embolism risk scores

Abstract: This retrospective cohort study compared the diagnostic utility (sensitivity, specificity and negative predictive value (NPV)) of the age-times-10 adjusted d-dimer cut-off used in combination with the original and simplified Well's pulmonary embolism (PE) scores and the original and simplified revised Geneva scores to identify patients in whom PE is classified as unlikely according to each score. The PE risk scores performed similarly with high sensitivity (97.6, 97.1, 96.9 and 97.1% respectively) and NPV (99.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Our study findings confirmed that all three predictive tools have excellent and comparable negative predictive value when combined with D-dimer regardless of the D-dimer threshold [14,34]. The highest sensitivity to rule out PE was observed with the combination of low CP per YEARS algorithm with D-dimer < age-adjusted cut-off (83%) and the combination of low CP per Well's score and D-dimer < age-adjusted cut-off (82%).…”
Section: Discussionsupporting
confidence: 79%
“…Our study findings confirmed that all three predictive tools have excellent and comparable negative predictive value when combined with D-dimer regardless of the D-dimer threshold [14,34]. The highest sensitivity to rule out PE was observed with the combination of low CP per YEARS algorithm with D-dimer < age-adjusted cut-off (83%) and the combination of low CP per Well's score and D-dimer < age-adjusted cut-off (82%).…”
Section: Discussionsupporting
confidence: 79%
“…All patients in the present study were successfully treated, but required a peripherally inserted central catheter and a prolonged course of IV meropenem through our ambulatory parenteral antibiotic programme. Whether there were specific bacterial virulence phenotypes or genetic polymorphisms 15 to account for the absence of severe invasive disease remains the focus of further study of these isolates.…”
Section: Brief Communicationsmentioning
confidence: 99%
“…As a result, information regarding the ability to rule out VTE based on a D-dimer assay, with or without CDRs, in hospitalized patients is scarce 9 , 10 . The use of age-adjusted D-dimer (AADD) was well-validated in several studies in the recent decade 11 – 13 , and it is used in combination with varied risk assessment scores for pulmonary embolism (PE) 14 .…”
Section: Introductionmentioning
confidence: 99%